Microparticles Novel Mechanisms of Intracellular Communication: Implication in Health and Disease - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2011)
BACKGROUND: The prevailing view that eukaryotic cells are restrained from intercellular exchange of genetic information has been challenged by recent reports on nanotubes, exosomes, apoptotic bodies, and nucleic acid—binding peptides that provide novel pathways for cell—cell communication, with implications in health and disease.CONTENT: Microparticles (MPs) are a heterogeneous population of small plasma membrane structures that serve as important signaling structures between cells. MPs are composed of a phospholipid bilayer that exposes transmembrane proteins and receptors and encloses cytosolic components such as enzymes, transcription factors, and mRNA derived from their parent cells. Growing evidence suggests that MPs regulate inflammation, stimulate coagulation, affect vascular functions and apoptosis, and can also play a role in cell proliferation or differentiation. MPs circulate in the bloodstream, can be detected in the peripheral blood, and may originate from different vascular cell types (eg, platelets, monocytes, endothelial cells, red blood cells, and granulocytes).SUMMARY: Cells of various types release small membrane vesicles called MP on their activation, as well as during the process of apoptosis. The properties and roles of MP generated in different contexts are diverse and are determined by their parent cell and the pathway of their generation, which affects their content. MP are involved in multiple cellular functions, including immunomodulation, inflammation, coagulation, and intercellular communication. MPs are able to deliver molecular signals in the form of lipids, proteins, nucleic acids, or functional trans-membrane proteins from the parent cell to distantly located targets. From a clinical point of view, MP may serve as biomarkers for disease status and may be found useful for developing novel therapeutic strategies.KEYWORDS: microparticles, microvesicle, membrane remodeling, Intercellular communication